Radical radiotherapy in older patients with muscle invasive bladder cancer. Issue 2 (March 2019) - Wujanto, Caryn; Tey, Jeremy; Chia, David; Ho, Francis; Ooi, Kiat Huat; Wong, Alvin S.; Soon, Yu Yang; Lim, Keith
Abstract: Background: Muscle invasive bladder cancer (MIBC) is prevalent in the older patients, who are a vulnerable population with multiple co-morbidities and at increased risk of complications. Radical cystectomy is often not suitable, hence radical radiotherapy (RT) is an alternative option. We reviewed the outcomes of older patients treated with RT with or without concurrent chemotherapy (CRT) at our institution. Methods: We retrospectively reviewed patients aged 65 years and above treated with radical RT for MIBC at our institution between March 2002 to January 2017. Data was collected from institutional medical records and RT databases. The primary outcome was 2- and 5-year overall survival (OS), recurrence free survival (RFS), and toxicities. Univariate cox proportional hazard regression models were performed to identify independent factors with significant impact on survival. Results: We identified 45 patients (34 males, 11 females) with a median age of 77 years (range 65–95). All patients received maximal transurethral resection of the bladder tumour prior to RT. Median dose of total RT was 64 Gy (range 50–69.8 Gy). Twenty one patients (47%) received CRT. Planned treatment was completed in 42 (93.3%) patients. Median follow-up was 31 months (range 1–147 months). The 2- and 5-year OS was 64% and 44%, respectively. The 2- and 5-year RFS was 68% and 49%, respectively. Median RFS was 34 months (range 8–121 months). Median OS was 56 months (range 18–100 months). Univariate analysis showed that performance status (0–1 vs. 2–3; HR 2.7, 95% CI 1.07–6.8, p = 0.035) and International Society of Geriatric Oncology (SIOG) group (≤2 vs. >2; HR 3.23, 95% CI 1.12–8.64, p = 0.019) were significantly associated with increased hazard for death. One patient (2%) had grade 3 cystitis. Conclusion: Radical RT is well tolerated in older patients with MIBC. We report outcomes similar to published data. Older patients should be considered for curative treatment despite their age. However, careful selection is warranted as frail patients (PS ≥2; SIOG >2) may benefit less.